How to improve consumers' understanding of online legal information: insights from a behavioral experiment - Alexander J. Wulf; Ognyan Seizov (European Journal of Law and Economics, 2022)
Past research has shown that online information notices often fail to inform consumers well, even if transparency-enhancing measures are implemented. However, the studies in question have employed research designs that were restricted to pre-contract conclusion scenarios and ad hoc, text-only attempts to optimize disclosures. While these results point to the general limitations of disclosures, they leave open whether optimizing information notices can be of substantial value to consumers in other settings. Our study tests the effectiveness of multimodal disclosure optimization techniques in both the pre- and post-contract conclusion scenarios. The post-contract conclusion scenario is the situation where a consumer has a dispute with a business. While this setting is not the primary target of disclosure legislation, it is a more realistic instance of the actual use of legal information online. Here the consumer has a real incentive to obtain information about his or her rights and obligations. We show that under these conditions, consumers do in fact read, retain and understand more when the attempt has been made to optimize disclosures.
Keywords: D12; D18; D83; K12; K20; 340; Information disclosure; Terms and conditions; Consumer contract law; Consumer protection; Transparency; Behavioral experiment